Expression of Listeria monocytogenes key virulence genes during growth in liquid medium, on rocket and melon at 4, 10 and 30 °C. (May 2016) - Hadjilouka, Agni; Molfeta, Christina; Panagiotopoulou, Olga; Paramithiotis, Spiros; Mataragas, Marios; Drosinos, Eleftherios H.
Abstract: The aim of the present study was to assess the expression of key virulence genes, during growth of a Listeria monocytogenes isolate in liquid medium, on melon and rocket at different temperatures and time. For that purpose, BHI broth, rocket and melon were inoculated at 7.0–7.5 log CFU mL −1 or g −1 and stored at 4, 10 and 30 °C. Sampling took place upon inoculation and after 0.5, 6 and 24 h of incubation. The RNA was stabilized and the expression of hly, plcA, plcB, sigB, inlA, inlB, inlC, inlJ, lmo2672 and lmo2470 was assessed by RT-qPCR. The results obtained were summarized into two observations; the first one referring to the interactive effect of incubation temperature and type of substrate and the second one to the effect of time on gene expression. Regarding the latter, nearly all genes were regulated upon inoculation and exhibited differential expression in the subsequent sampling times indicating the existence of additional regulatory mechanisms yet to be explored. Highlights: Interactive effect of incubation temperature and type of substrate on key virulence gene expression. Regulation by all genes upon inoculation. Different gene expression in the subsequent sampling times.